Clinical and molecular characterization of patients with stage 4(M) neuroblastoma aged less than 18 months without MYCN amplification. Issue 8 (7th April 2021) - Berthold, Frank; Rosswog, Carolina; Christiansen, Holger; Frühwald, Michael; Hemstedt, Nadine; Klingebiel, Thomas; Fröhlich, Birgit; Schilling, Freimut H.; Schmid, Irene; Simon, Thorsten; Hero, Barbara; Fischer, Matthias; et al.
Abstract: Introduction: The survival of children with stage 4(M) neuroblastoma without MYCN amplification and below the age of 18 months is considered better than the still dismal outcome of older high‐risk neuroblastoma patients. This study analyzes the impact of clinical and molecular characteristics on the long‐term outcome. Patients and methods: Clinical presentation, survival, and recurrence patterns of patients enrolled onto trials NB90, NB97, and NB2004 were retrospectively analyzed. Gene expression signatures based on RNA microarrays (TH10) were investigated if tumor material was available. Results: Between 1990 and 2015, 177 patients with stage 4(M) MYCN nonamplified neuroblastoma aged less than 18 months at diagnosis were eligible. After a median follow‐up of 9.7 years (IQR 5.0, 13.4), the proportions of 10‐year event‐free survival (EFS) and overall survival (OS) were 73% (95% confidence interval [CI] 67–79%) and 86% (95% CI 80–92%), respectively. Of the 27 neuroblastoma recurrences, 44% occurred in more than one site. Four additional patients presented histologically mature ganglioneuroma at recurrence. Six patients developed a secondary malignancy. The secondary 5‐year EFS and OS of the 27 patients with neuroblastoma recurrence were 44% and 59%, respectively. TH10 gene expression signature was not prognostically predictive in the investigated subcohort. Conclusion: The outcome of patients with stage 4(M) neuroblastoma aged less than 18 months is favorable when treated with high‐risk or otherwise intensive therapy. The development of secondary malignancies and the potential of maturation to ganglioneuroma call for a controlled stepwise reduction of treatment intensity.